The effect of African Easterly Wave suppression by periodicity on Atlantic tropical cyclones - Derrick K Danso; Christina M Patricola; Emily Bercos-Hickey; Christophe Lavaysse (Environmental Research Letters, 2025)
Research has shown that suppressing African Easterly Waves (AEWs) does not reduce basin-wide North Atlantic tropical cyclone (TC) frequency but can enhance TC environmental favorability. We investigated the AEW-TC relationship further by examining the effects of suppressing the two AEW periodicities individually on TC activity. Using regional model simulations, AEWs were prescribed or suppressed in the 2–6 d or 6–10 d ranges through the lateral boundary conditions. Seasonal TC frequency increased significantly when either AEW periodicity was suppressed, with a larger increase when the 2–6 d waves were suppressed. We also found that suppressing the 2–6 d waves increased mid-tropospheric moisture by up to 8%, as well as overall atmospheric instability, near the western coast of northern Africa. Furthermore, the convective disturbances that developed into TCs exhibited stronger rotation, increased ascending motion, and higher rainfall. Our results suggest that reduced 2–6 d AEW activity may trigger a more active TC season.